Evaluation of supervision as the role of the principal and its impact on improving the quality of teaching and learning activities in elementary schools: a literature review study - Laila Nurul Wahidah; Nunuk Hariyati; Ayu Wulandari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Evaluation of Supervision as the Role of the Principal and Its Impact on Improving the Quality of Teaching and Learning Activities in Elementary Schools: A Literature Review Study Background: The quality of teaching and learning activities in elementary schools is a fundamental pillar of education, the success of which is heavily influenced by the principal's role as an academic supervisor. However, supervision is often perceived merely as an administrative formality. Objective: This study aims to evaluate the implementation of supervision by principals and analyze its impact on improving the quality of teaching and learning activities at the elementary level through a systematic literature review. Methods: The method used is a Systematic Literature Review (SLR). The article selection process followed the PRISMA protocol across Google Scholar, SINTA, and Garuda databases within the 2020–2025 timeframe. Fifteen selected articles were analyzed using data extraction and thematic synthesis techniques. Results: Findings indicate that clinical supervision and classroom visitations are the most effective methods for enhancing teacher professionalism. Supervisory evaluation has a significant impact on innovative teaching methods, orderly instructional administration, and increased student engagement in class. Conclusion: Supervision that is carried out consistently, collaboratively, and followed by concrete follow-up is proven to sustainably transform the quality of teaching and learning activities in elementary schools.